Enhancing Gas Turbine Fault Diagnosis Using a Multi-Scale Dilated Graph Variational Autoencoder Model - Kun, Zhang; Hongren, Li; Xin, Wang; Daxing, Xie; Shuai, Yang (IEEE access, 2024)
This paper proposes a Multi-scale Dilated Variational Graph Convolutional Autoencoder (MG-VAE) model for gas turbine fault diagnosis. The model integrates a multi-scale dilated convolutional attention mechanism to extract features across different scales, enhancing its ability to represent complex data and improving robustness in noisy environments. Additionally, a graph convolution module captures correlations between sensors, further enhancing diagnostic accuracy. Experimental results demonstrate the model's effectiveness, achieving high diagnostic accuracy in both gear fault simulation and real gas turbine fault datasets. Ablation experiments show that the integration of the graph convolutional network and the multi-scale dilated convolutional attention mechanism significantly improves accuracy, highlighting the model's potential for practical industrial applications in gas turbine fault diagnosis.